The Effect of Learning Interest on The Results of Learning to Write Poetry Text using Problem Based Learning Method - Ratna Suminar (JLER (Journal of Language Education Research), 2022)
This study aims to prove the effect of interest in learning with the results of learning to write poetry texts using the problem based learning method. The hypothesis tested is that there is an influence of interest in learning on writing poetry texts. The research subjects were 29 students of class VIII F MTs Negeri 2 Subang, West Java, in the 2020/2021 school year. The data comes from the results of learning to write poetry texts and the results of a learning interest questionnaire. Data were analyzed using SPSS 25 with product moment person correlation test to determine the relationship and regression test to determine the effect. Based on the results of statistical analysis, the results of the correlation test of 89.2% showed a very strong relationship between the results of learning to write poetry texts with interest in learning. The results of the regression test also prove that interest in learning has an effect of 79.5% on learning outcomes to write poetry texts. Meanwhile, 20.5% was influenced by other factors.  ABSTRAKPenelitian ini bertujuan untuk membuktikan pengaruh minat belajar dengan hasil belajar menulis teks puisi menggunakan metode problem based learning. Hipotesis yang diuji yaitu terdapat pengaruh minat belajar terhadap menulis teks puisi. Subjek penelitian adalah 29 orang siswa kelas VIII F MTs Negeri 2 Subang, Jawa Barat, tahun ajaran 2020/2021. Data bersumber dari hasil belajar menulis teks puisi dan hasil angket minat belajar. Data dianalisis menggunakan SPSS 25 dengan uji korelasi product moment person untuk mengetahui hubungan dan uji regresi untuk mengetahui pengaruh. Berdasarkan hasil analisis statsitik, hasil uji korelasi sebesar 89,2% menunjukan hubungan yang sangat kuat antara hasil belajar menulis teks puisi dengan minat belajar. Hasil uji regresi juga membuktikan minat belajar berpengaruh sebesar 79,5% terhadap hasil belajar menulis teks puisi. Sementara 20,5% itu dipengaruhi oleh faktor lainnya.